Introduction of an Electronic Mobile Device Version of an Alcohol Impairment Scale (the Hack's Impairment Index Score) Does Not Impair Nursing Assessment of Patients in Emergency Departments - Jason B. Hack, MD; Dennis Ferrante; Janette Baird, PhD (Elsevier, 2021)
ABSTRACT: Background: There is no formal assessment to determine level of disability in the millions of patients with alcohol-induced impairment who present to emergency departments annually. Hack's Impairment Index (HII) is a standardized, serializable clinical tool designed to quantify ability. Nursing staff members at this center perform the HII and determine a score using paper prompts. Objective: We developed an HII electronic application and investigated whether or not an electronic version on a mobile device would affect nursing performance. Methods: A chart review-based quality improvement project compared the number, repetitions, and completeness of HII score documentation performed by nurses over 6.5 months. Group 1: paper-based HII scores for the 90-day period before intervention; group 2: iPad-based HII scores for the 90 days after intervention. There was a 2-week period for staff training and electronic version feedback between groups. Informal, ad hoc interviews were performed with nurses at investigation termination. Results: Group 1: 476 emergency department patients with alcohol-induced impairment had HII scores ordered; 339 (71.2%; 95% CI, 67.1, 75.3%) had HII assessments with a total of 539 HII scores documented. An average (SD) 1.60 (0.01) serial assessments occurred per patient, 5 (1.1%; 95% CI, (0, 2.2%) scores were incomplete. Group 2: 569 alcohol-induced impairment emergency department patients were seen and had HII scores ordered; 420 (73.8%; 95% CI, (70.2, 77.4%) had HII assessments with a total of 639 HII scores documented. An average (SD) 1.52 (0.03) serial assessments occurred per patient, 4 (0.9%; 95% CI, (0.81, 0.99%) had incomplete HII scores. Conclusions: Although our study took place at 1 center, was a chart review, and not directly observed, we found that the mobile device-based HII application to determine a score did not interfere with nursing performance. Specifically, the repetition and completeness of nursing assessments of emergency department patients with impairment from alcohol use was not altered when comparing paper chart documentation with electronic format documentation. (Curr Ther Res Clin Exp. 2021; 82:XXX-XXX)